Civic ideology, organization, and law in the Rule scrolls : a comparative study of the Covenanters' sect and contemporary voluntary associations in political context - Gillihan, Yonder Moynihan. (Studies on the Texts of the Desert of Judah, 2012)
Over the past sixty years, several studies have demonstrated that the Dead Sea Scrolls sect was one of numerous voluntary associations that flourished in the Hellenistic-Roman age. Yet the origins of organizational and regulatory patterns that the sect shared with other associations have not been adequately explained. Drawing upon sociological studies of modern associations, this book argues that most ancient groups appropriated patterns from the state. Comparison of the Rule Scrolls with Greco-Roman constitutional literature, as well as philosophical, rabbinic, and early Christian texts, shows that the sect's appropriation helped articulate an \'alternative civic ideology\' by which members identified themselves as subjects of a commonwealth alternative and superior to that of the status quo. Like other associations with alternative civic ideology, the Covenanters studied constitution and law with the intention of reform, anticipating governance of restored Israel at the End of Days.